Innovations in the Portuguese local government: Contributions for local democracy - Almeida, M. A. (Sociologia, Problemas e Práticas, 2022)
In Portugal important legal innovations have been introduced in local government, related to the problems of negative images associated with longevity and corruption, and a decrease in voters’ turnout. Independent local lists were introduced into the race in the form of citizen groups, mayors’ terms were limited to three and there was a parity law. Participative budgets and decentralized local council meetings have also provided new tools for citizen participation. The object was to discuss whether these innovations are real contributions for local democracy. Methodology included the analysis of the legislative process and its enforcement, and practical consequences, namely on new representatives and citizen participation.